Optimasi Laju Alir Produksi Sumur Gas R-09 Menggunakan Metode Modified Isochronal Test, Turner dan Mayer-Gardner - Riski, Firmansyah; Hanafi, Rosmalina; Muthalib, irwan Setiawan (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2022)
To find out the ability of a well in production, it is necessary to conduct a Well Test. Well Testing can be done by several methods, one of which is a Deliverability Test where this test is carried out to find out the value of AOFP (Absolute Open Flow Potential) of a well with supporting data from the results of the Modified Isochronal Test of the R-09 well obtained. The maximum flow rate of R-09 wells can be calculated after being calculated at 25-30% AOFP. In addition, the calculation of the maximum critical flow rate is carried out to avoid the occurrence of water coning because it can cause the water level in the reservoir to increase so that water is also produced. Then the turner rate calculation is done which is the minimum flow rate limit to avoid liquid loading so that liquid does not fall into the perforation area due to the flow rate that is not enough to lift liquid so that it can cause obstruction of gas production because liquid collects in the perforation area. Therefore, this study was conducted to find out what the optimal production value is so that there is no water coning and liquid loading by calculating the right size of bean choke and then optimizing the bean choke gas so that the flow rate is in accordance with production needs.